Problems Faced by English Majors in Translating Collocations from English into Arabic - Abdulmunam Ramadan Mohammed Swesi (Journal of Scientific and Human Dimensions, 2025)
The translation of collocation is tough for non-native speakers of a language and creates many problems for students, teachers and translators. The present study aimed to determine, examine and investigate the strategies and techniques adopted by students in translating collocations from English to Arabic. The data examined here, consisted of  a translation test that comprised 9 relatively short sentences of a contextual collocations  selected from different sources. Students were required to translate these collocations from English to Arabic according to Newmark approach (semantic & communicative approaches). So, the findings and results have shown that, students used or resorted  various strategies in order to overcome the problems of rendering certain collocation expressions. In addition, the knowledge of  collocation leads to the improvement of oral proficiency, listening comprehension, and reading speed.
Keywords: Collocation; English Majors; Translation; Semantic translation; Communicative translation